Building Cyber Resilience to Face the Challenges of Cognitive Warfare - Radu, Raluca (European Conference on Cyber Warfare and Security, 2025)
In the context of strategic ambiguity characterizing the geopolitical landscape of the past two years, cyber resilience plays a vital role in advancing alliances' deterrence and defense goals while minimizing the effects of cognitive warfare. The EU addresses cyber resilience by implementing mandatory cybersecurity requirements to ensure the development of secure digital products, significantly reducing vulnerabilities that impact businesses (EU, 2020; EU, 2022). In contrast, NATO prioritizes cybersecurity in the context of communication systems and information-sharing frameworks, while encouraging member states to bolster their cyber defense capabilities (NATO, 2024). However, the susceptibility of the human factor as a target of cognitive warfare conducted through cyberattacks is not explicitly addressed in international cybersecurity policies. This theoretical research aims to identify methods and tools to enhance cyber resilience in response to the challenges of cognitive warfare. Through the available literature, this paper establishes the conceptual framework for understanding cyber resilience and cognitive warfare. Using observation as a research method, we identified a series of similarities in NATO and EU programs and strategies targeting the cognitive dimension, including measures aimed at countering disinformation, fostering resilience against psychological manipulation, and enhancing information-sharing protocols among member states. While the Alliances remain at the forefront of cyber defence, there is still room for improvement. To enhance cyber and organizational resilience, Romania's specialized cyber defense structures employ strategies focused on raising civil society awareness, integrating adaptability into the education system, and fostering effective communication and collaboration both within and across public institutions. The key observation presented in this study is that a comprehensive approach to building cyber resilience is essential not only for enhancing deterrence and defense capabilities, but also for effectively countering the multifaceted impacts of cognitive warfare, which increasingly exploit vulnerabilities in digital networks, information systems, and public perception. Furthermore, this serves as an initial step in a PhD research thesis aimed at offering states solutions for enhancing cyber resilience, with the goal of safeguarding their citizens from the challenges posed by cognitive warfare.